Evektivitas Cognitif Behavioral Therapy (CBT) dalam Mengelola Emosi Negatif pada Warga Binaan Perempuan di Lembaga Permasyarakatan - Firlia, Nur Akni; Sujarwo, Sawi (Jurnal Konseling dan Psikologi Indonesia, 2025)
Female inmates in correctional institutions often experience severe psychological pressure, particularly in the form of negative emotions such as anxiety, anger, guilt, and despair. If left unaddressed, these conditions can hinder rehabilitation and personal development. Cognitive Behavioral Therapy (CBT) is a therapeutic approach that focuses on restructuring maladaptive thoughts and behaviors. This study explores the effectiveness of CBT in managing negative emotions among female inmates using a qualitative case study approach. Fourteen participants joined group counseling sessions, while three individuals received focused CBT interventions such as emotional journaling, guided discovery, self-affirmation, and cognitive restructuring. The findings indicate significant improvements in emotional expression, reduced self-harming tendencies, and increased awareness of negative automatic thoughts. Supportive activities such as art therapy and reflective discussions strengthened the recovery process. The effectiveness of CBT was enhanced by active participant engagement, spiritual integration, and social support from the correctional environment. CBT has proven to provide a safe space for inmates to reconstruct their self-meaning and develop sustainable emotional regulation skills. Therefore, integrating CBT into rehabilitation programs for female inmates is highly recommended to enhance psychological well-being and social reintegration readiness.